2023
DOI: 10.7759/cureus.36826
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice (KAP) of COVID-19 Vaccine Among Saudi Mothers

Abstract: Background: The coronavirus disease 2019 (COVID-19) vaccine is a novel vaccine that was created during the midst of the COVID-19 pandemic in 2020 to combat the highly contagious COVID-19 infection. Since the initiation of vaccine administration campaigns globally, lots of research was simultaneously being done to study the vaccine's side effects and possible complications, especially in vulnerable groups such as pregnant women and children. Saudi Arabia is one of the leading countries in administering the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…These results align with studies conducted in Oman [ 33 ] and Bosnia [ 55 ], where a significant correlation was observed between higher knowledge levels and positive attitudes towards vaccination. In line with other studies [ 55 , 56 ], participants with higher knowledge scores were significantly more likely to participate in vaccination programs. Similarly, this study found that individuals with lower knowledge levels or negative attitudes were more likely to demonstrate negative or indifferent practices towards vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…These results align with studies conducted in Oman [ 33 ] and Bosnia [ 55 ], where a significant correlation was observed between higher knowledge levels and positive attitudes towards vaccination. In line with other studies [ 55 , 56 ], participants with higher knowledge scores were significantly more likely to participate in vaccination programs. Similarly, this study found that individuals with lower knowledge levels or negative attitudes were more likely to demonstrate negative or indifferent practices towards vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…A noteworthy finding from a study carried out in Riyadh, Saudi Arabia, was the considerable hesitancy rate, with one-third of parents expressing unwillingness to vaccinate their children against COVID-19. 25 This study underscored the significant influence of social media as a factor, emphasizing the importance of implementing targeted communication strategies.…”
Section: Research Insights and Existing Gapsmentioning
confidence: 82%
“…Knowledge questions were five, translating into a total score of 5, while the attitude questions were four, translating into a score of 4. After calculating the knowledge and attitude scores, participants who scored 3/5 (60%) were considered to have good knowledge and those who scored 2/4 (50%) were considered to have a positive attitude [30] [76] [77]. A chi-square test was used to determine the relationship between categorical variables.…”
Section: Discussionmentioning
confidence: 99%